Antioxidant and antihypertensive properties of phenolic–protein complexes in extracted protein fractions from Nigella damascena and Nigella arvensis. (May 2016) - Alu'datt, Muhammad H.; Rababah, Taha; Alhamad, Mohammad N.; Gammoh, Sana; Ereifej, Khalil; Alodat, Moh'd; Hussein, Neveen M.; Kubow, Stan; Torley, Peter J.
Abstract: The study involved the investigation of the antioxidant and antihypertensive properties of the phenolic–protein complexes obtained from isolated protein fractions from Nigella damascena and Nigella arvensis . Protein fractions from flours made from the seeds of Nigella species were isolated and included albumin, globulin, glutelin-1, glutelin-2 and prolamin. Albumin and glutelin-1 fractions were the predominant proteins in the two Nigella species studied in terms of protein content and percent protein yield. Free phenolics were extracted from the isolated protein fractions by methanol treatment at either 25 °C or 60 °C followed by acid and base hydrolysis to obtain bound phenolics. The free and bound phenolic composition was assessed by RP-HPLC. The highest phenolic content was observed in the free phenolic extract at 25 °C (FP-25 °C) in glutelin-2 of both Nigella species. The free and bound phenolics of the protein fractions were tested for angiotensin converting enzyme (ACE) inhibitory and antioxidant activities. The greatest ACE inhibitory activities were seen for the free and bound phenolic extracts obtained from glutelin-2 and globulin fractions of both Nigella species. The highest antioxidant activities were observed in the extracted phenolics from glutelin-1 and globulin from N. damascena and albumin from N. arvensis . Only a weak correlation was seen between the phenolic content of the isolated protein fractions and the ACE inhibitory and antioxidant activities. The present study indicates that phenolic–protein complexes in the Nigella species have significant antioxidant and ACE inhibitory properties although the bioactivities of the protein fractions are not closely related to their total phenolic content. Graphical abstract: Highlights: Major predominant protein fractions in Nigella sp were albumin and glutelin-1 fractions. Highest content of free phenolics in glutelin-2 fractions of Nigella sp. Highest ACE inhibitory activity in free phenolics from globulin fraction in Nigella arvensis . No correlations between contents and biological properties of phenolics in protein fractions.